Managing fast- vs. slow-growth genotypes to optimize quality and yield grades - R.R. Schalles; K.O. Zoellner; Michael E. Dikeman (Kansas Agricultural Experiment Station Research Reports, 1989)
Fast-growth genotype steers placed on a high energy ration a month after weaning were compared to a slow-growth genotype on a growing ration for 155 days, followed by a finishing ration for 62 days. The fast-growth genotype produced heavier, higher quality carcasses in less time than the slow-growth genotype, with similar energy conversion. Using contemporary prices. the fast-growth genotype cattle broke even, and the slow-growth genotype lost 124 per head.
Keywords: Cattlemen& #x27; s Day; 1989; Kansas Agricultural Experiment Station contribution; no. 89-567-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 567; Beef; Genotypes; Quality grades; Yield grades